Pediatric Shoulder Arthroscopy is Effective and Most Commonly Indicated for Instability, Obstetric Brachial Plexus Palsy, and Partial Rotator Cuff Tears - Nareena Imam, B.A; Suleiman Y. Sudah, M.D; Joseph E. Manzi, M.D; Christopher R. Michel, M.D; Dane M. Pizzo, M.S; Mariano E. Menendez, M.D; Allen D. Nicholson, M.D (Elsevier, 2023)
Purpose: The purpose of this review was to systematically evaluate the literature on pediatric shoulder arthroscopy and outline its indications, outcomes, and complications. Methods: This systematic review was carried out in accordance with PRISMA guidelines. PubMed, Cochrane Library, ScienceDirect, and OVID Medline were searched for studies reporting the indications, outcomes, or complications in patients undergoing shoulder arthroscopy under the age of 18 years. Reviews, case reports, and letters to the editor were excluded. Data extracted included surgical techniques, indications, preoperative and postoperative functional and radiographic outcomes, and complications. The methodological quality of included studies was evaluated using the Methodological Index for Non-Randomized Studies (MINORS) tool. Results: Eighteen studies, with a mean MINORS score of 11.4/16, were identified, including a total of 761 shoulders (754 patients). Weighted average age was 13.6 years (range, 0.83-18.8 years) with a mean follow-up time of 34.6 months (range, 6-115). As part of their inclusion criteria, 6 studies (230 patients) recruited patients with anterior shoulder instability and 3 studies recruited patients with posterior shoulder instability (80 patients). Other indications for shoulder arthroscopy included obstetric brachial plexus palsy (157 patients) and rotator cuff tears (30 patients). Studies reported a significant improvement in functional outcomes for arthroscopy indicated for shoulder instability and obstetric brachial plexus palsy. A significant improvement was also noted in radiographic outcomes and range of motion for obstetric brachial plexus palsy patients. The overall rate of complication ranged from 0% to 25%, with 2 studies reporting no complications. The most common complication was recurrent instability (38 patients of 228 [16.7%]). Fourteen of the 38 patients (36.8%) underwent reoperation. Conclusion: Among pediatric patients, shoulder arthroscopy was indicated most commonly for instability, followed by brachial plexus birth palsy, and partial rotator cuff tears. Its use resulted in good clinical and radiographic outcomes with limited complications. Level of Evidence: Systematic review of Level II to IV studies.